The effect of capital intensity, leverage, liquidity, moderated by company size on tax agressiveness (Empirical study on energy companies listed on the Indonesia Stock Exchange for the 2018-2022 period) - Tassha Billy Gunawan; Agoestina Mappadang (Goodwood Publishing, 2024)
Purpose: This study examines the effect of capital intensity, leverage, and liquidity on tax aggressiveness and profitability as moderating variables of tax aggressiveness. Research methodology: This study used energy companies listed on the Indonesia Stock Exchange, selected using the purposive sampling method from 2018 to 2022 and there were 23 companies chosen. The data analysis in this study used panel data regression. Results: Capital intensity negatively affects tax aggressiveness; leverage and liquidity have no effect on tax aggressiveness; company size can moderate the effect of capital intensity on tax aggressiveness, but company size cannot moderate the effect of leverage and liquidity on tax aggressiveness. Conclusions: Audit quality is strongly influenced by the competence and professionalism of internal auditors, while independence contributes positively but not significantly. Ensuring high competence and professionalism enhances the credibility and reliability of government audit. Limitations: The study was limited to one BPKP representative office with a relatively small sample size, which may restrict the generalizability of the findings to other BPKP offices. Contribution: This research provides empirical evidence for improving audit quality by strengthening the competence and professionalism of internal auditors, offering valuable insights for audit institutions and policymakers to enhance government accountability.